Skill Entrepreneur dalam Meningkatkan Profitabilitas Pedagang Muslim di Pasar Sumput Driyorejo Gresik - Sutono Sutono; Sofia Sofia (Universitas Islam Lamongan, 2021)
Abstract: Skills in the world of entrepreneurship are the characteristics, traits, knowledge, and abilities that underlie a person in working and operating everything related to the tasks being carried out so that their performance is adequate. The purpose of this study is to describe entrepreneur skills in increasing the profitability of Driyorejo Muslim traders. This study hopes to obtain a new concept about the importance of entrepreneurship skills for Muslim traders in the Sumput market Driyorejo in increasing profitability in a sustainable business. Descriptive analysis is used to describe the condition of the research object. This study is a causality study that is used to measure the strength of the relationship between two or more variables, as well as to show the direction of the relationship between the independent variable and the dependent variable or to question the cause and effect between variable X and variable Y. This is evidenced through simple regression analysis and based on the results hypothesis testing using the T-test, it is found that Ho is rejected and Ha is accepted, which means that there is an influence between entrepreneurial skills on business profitability. Based on the results of this research, entrepreneurial skills influence the profitability of Driyorejo Muslim traders, Gresik regency.